Democracy and decentralization : a policy perspective on Nepal from POLSAN Seminar - Thapa, Ganga B. (Kathmandu : Political Science Association of Nepal, 1996)
Proceedings of the National Seminar on Strengthening Participatory Democracy through Decentralization.
Includes bibliographical references.
Keywords: Decentralization in government -- Nepal -- Congresses; Local government -- Nepal -- Congresses; Nepal -- Politics and government -- Congresses